Graphene nanoribbons with mixed cove-cape-zigzag edge structure. (30th April 2021) - Shinde, Prashant P.; Liu, Jia; Dienel, Thomas; Gröning, Oliver; Dumslaff, Tim; Mühlinghaus, Markus; Narita, Akimitsu; Müllen, Klaus; Pignedoli, Carlo A.; Fasel, Roman; Ruffieux, Pascal; Passerone, Daniele
Abstract: A recently developed bottom-up synthesis strategy enables the fabrication of graphene nanoribbons with well-defined width and non-trivial edge structures from dedicated molecular precursors. Here we discuss the synthesis and properties of zigzag nanoribbons (ZGNRs) modified with periodic cove-cape-cove units along their edges. Contrary to pristine ZGNRs, which show antiferromagnetic correlation of their edge states, the edge-modified ZGNRs exhibit a finite single particle band gap without localized edge states. We report the on-surface synthesis of such edge-modified ZGNRs and discuss tunneling conductance dI/dV spectra and dI/dV spatial maps that reveal a noticeable localization of electronic states at the cape units and the opening of a band gap without presence of edge states of magnetic origin. A thorough ab initio investigation of the electronic structure identifies the conditions under which antiferromagnetically coupled, edge-localized states reappear in the electronic structure. Further modifications of the ribbon structure are proposed that lead to an enhancement of such features, which could find application in nanoelectronics and spintronics. Graphical abstract: Image 1